The Parents’ Role in Children’s Learning Process During the Covid-19 Pandemic - Putri Dini Meutia; Riki Musriandi; Haris Mustafa (STAI Hubbulwathan Duri, 2022)
This study aimed to determine the parents’ roles in developing children learning during Distance Learning (PJJ). The descriptive quantitative method was used in this research. The population of this study was all parents of students at two public elementary schools in Kuta Baro District, Aceh Besar. The sample of this research was 137 parents. The sampling technique was random sampling. The research instrument used was a questionnaire. The questionnaire was distributed via Google Forms. The data was analyzed by using percentages. The study results indicated that the parents’ roles were in the Good category. Most parents agreed that giving their time and providing can improve their children's learning during a pandemic and strengthen their relationships. Moreover, the recent education level and occupation of the parents also influenced the role of parents during distance learning.